PENERIMAAN OPINI AUDIT GOING CONCERN BERDASARKAN LEVERAGE DAN FINANCIAL DISTRESS - Rahman, Huda Aulia (Jurnal Ekonomi : Journal of Economic, 2020)
AbstractThe purpose of this study is to determine the impact of leverage and financial distress on going concern audit opinions of mining sector companies listed on the Indonesia Stock Exchange (IDX) with the 2012-2017 research period. Leverage was proxied using debt to asset ratio (DAR), and financial distress was proxied using Altman Z-Score. The object of this research used were 17 mining sector companies selected based on the random purposive sampling method. This study used data processing logistic regression analysis using SPSS version 25. The results of this research was financial distress have negative effect on going concern modification opinions, while leverage had no effect on going concern audit opinion.                         Keywords: Financial Distress, Leverage, Going Concern Audit Opinion